1996
DOI: 10.1083/jcb.132.6.999
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a cytoplasm to vacuole targeting determinant in aminopeptidase I.

Abstract: Abstract. Aminopeptidase I (API) is a soluble leucine aminopeptidase resident in the yeast vacuole (Frey, J., and K.H. Rohm. 1978. Biochim. Biophys. Acta. 527:31-41). The precursor form of API contains an amino-terminal 45-amino acid propeptide, which is removed by proteinase B (PrB) upon entry into the vacuole. The propeptide of API lacks a consensus signal sequence and it has been demonstrated that vacuolar localization of API is independent of the secretory pathway (Klionsky, D.J., R. Cueva, and D.S. Yaver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
0
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 57 publications
(76 reference statements)
8
106
0
3
Order By: Relevance
“…The intermediate band that appears following proteinase K digestion in the presence of detergent ( Figure 5B, top, lane 6) is thought to be due to an effect of detergent on the prApe1 conformation (Oda et al, 1996). From the above-mentioned observations, we concluded that Cvt18 is not required for the initial membrane association of prApe1, but it is involved in the membrane sequestration or enclosure stage of Cvt vesicle formation.…”
Section: Role Of Cvt18/gsa12 In Two Yeastsmentioning
confidence: 81%
“…The intermediate band that appears following proteinase K digestion in the presence of detergent ( Figure 5B, top, lane 6) is thought to be due to an effect of detergent on the prApe1 conformation (Oda et al, 1996). From the above-mentioned observations, we concluded that Cvt18 is not required for the initial membrane association of prApe1, but it is involved in the membrane sequestration or enclosure stage of Cvt vesicle formation.…”
Section: Role Of Cvt18/gsa12 In Two Yeastsmentioning
confidence: 81%
“…With regard to the details of cargo recognition, the Cvt pathway was the first well-studied type of selective autophagy in yeast; it is also the primary example of a biosynthetic rather than degradative use of autophagy [119][120][121][122]. The double-membrane sequestering vesicle is termed a Cvt vesicle rather than an autophagosome; as noted above, this vesicle contains selective cargos of the Cvt pathway, but excludes bulk cytoplasm, in accordance with the biosynthetic and constitutive nature of the Cvt pathway compared to starvation-induced autophagy.…”
Section: Cvt Pathwaymentioning
confidence: 99%
“…During the initial identification of the genes encoding the Atg proteins, several were classified as being specific for nonselective macroautophagy, the Cvt pathway and/or pexophagy. For example, Atg11 was originally characterized as being a Cvt pathway-specific protein (Harding et al 1996;Oda et al 1996). These denotations, however, reflected the different screens used to identify the corresponding genes and the limited analyses available at that time.…”
Section: Macroautophagymentioning
confidence: 99%